Heterlimnius luyashanensis sp. n. and Zaitzevia triangularis sp. n. from Shanxi Province, China (Coleoptera: Elmidae) - Peng, Yun-Fei; Bian, Dong-Ju; Wang, Ju-Ping (Zootaxa, 2024)
Two new species, Heterlimnius luyashanensis sp. n. and Zaitzevia triangularis sp. n. are described from Shanxi Province, China. The genus Heterlimnius Hinton, 1935 and Zaitzevia Champion, 1923 are reported from Shanxi Province for the first time. Heterlimnius luyashanensis sp. n. belonging to the Heterlimnius trachys species group has the following characteristics: 1. anterior margin of pronotum strongly produced anteriad; 2. median longitudinal sulcus of pronotum extends from basal 0.3 to 0.8. Zaitzevia triangularis sp. n. has a larger body size and a triangular apex of penis.